Spiritual Moderation for Early Childhood in Encouraging Tolerance Values - Agnes Novianti Permata Sari; Hermanda Ihut Tua Simamora; Melina Agustina Sipahutar; Goklas J Manalu; Epi Phania Napitupulu; Desi Elfriede Panggabean (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
Religious tolerance supports social peace and brings a better life to the country. Teaching tolerance in early childhood is a challenge for educators. The purpose of this study was to describe changes in the values of religious tolerance in elementary school students. This type of research is a type of qualitative research using a case study design where the researcher participates as an observer. The investigation begins with a documentary analysis of the research material. The next step is to conduct a focus group (FGD). This research resulted in findings that (a) changes in the values of inter-religious tolerance among elementary school (SD) children, especially children aged 6-8 years or grade two, on the basis of all students having the same religion, (2) changes in the values of tolerance between high-value children are taught through integrated learning, (3) while the values of tolerance between children are not specifically taught, values of togetherness such as greeting each other, sharing and supporting the needs of fellow children. taught through group practice. The conclusion of this study is that children quickly become comfortable with each other and form friendships with those who have the same characteristics, such as skin color, face shape, hair type, and even height.